Mature tertiary lymphoid structures in lung adenocarcinoma are associated with better progression free survival. (28th October 2021) - Obeng, R; Parihar, V; Alexis, D; Behera, M; Owonikoko, T; Pillai, R; Ramalingam, S; Sica, G; Ahmed, R
Abstract: Introduction/Objective: The presence of inducible lymphoid structures known as tertiary lymphoid structures in the tumor microenvironment has been shown to correlate with positive clinical outcome. However, the maturation states of lymphoid aggregates in lung adenocarcinoma are not completely understood. Methods/Case Report: Seventy tumor samples from 69 patients diagnosed with lung adenocarcinoma (Stages I to III) between 2013 and 2015 were included in the study. The presence and maturation states of the lymphoid structures within the tumors were evaluated by conventional and 26 samples were further analyzed by multiplexed immunohistochemistry of formalin fixed paraffin embedded tissues and then quantified. Mature lymphoid follicles containing germinal centers were identified by the presence of CD21+ and BCL-6+ cells in an organized configuration within tight clusters of T and B cells. Results (if a Case Study enter NA): Samples with fully mature lymphoid structures (germinal centers) had larger tumors and higher disease stage. The number of mature lymphoid structures correlated with the total number of lymphoid aggregates present in the tumor microenvironment. Additionally, tumor samples with ≥10 mature lymphoid structures had more primary follicles. While there was no difference in overall survival, progression free survival was significantly longer in patients who had ≥10 mature lymphoid structures in comparison with patients who had <10 mature structures. Conclusion: In conclusion, a spectrum of lymphoid aggregates in different stages of maturation are present in lung adenocarcinoma. An increase in the number of mature lymphoid structures may be associated with progression free survival in patients with lung adenocarcinoma.